1984
DOI: 10.1002/cm.970040102
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison of cellular motile systems

Abstract: Cellular motile systems as diverse as muscle and the mitotic spindle have been compared by their specific power output: the maximum power they develop per unit of engine volume. Striated muscles and flagella have high specific output; their performance is comparable to that of typical automobile engines. The cytokinetic furrow and the mitotic spindle have very much lower specific power output. The furrow's output is 7,000 times lower than muscle and the spindle's is 300,000 times lower. Different macromolecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…How powerful is this machine and how does it compare to other nanomachines? The performance of a machine over a range of sizes can be compared by power output or volume (Nicklas 1984(Nicklas , 1988 (Table 1). This measure includes force and velocity and, by including volume, reveals how concentrated the force generators are.…”
Section: Mechanical Properties Of the Major Spindle Components: Dna Amentioning
confidence: 99%
“…How powerful is this machine and how does it compare to other nanomachines? The performance of a machine over a range of sizes can be compared by power output or volume (Nicklas 1984(Nicklas , 1988 (Table 1). This measure includes force and velocity and, by including volume, reveals how concentrated the force generators are.…”
Section: Mechanical Properties Of the Major Spindle Components: Dna Amentioning
confidence: 99%
“…The performance of a machine over a range of sizes can be compared by power output/volume (88,89). This measure relates force and velocity to volume to reveal how concentrated force generators are.…”
Section: Weak Machines and Entropic Machinesmentioning
confidence: 99%
“…Motor proteins such as kinesin or dynein translocate microtubules on the order of microns/sec. The spindle sacrifices speed to prevent shear force that might damage DNA as well as for accuracy of segregation (88,89). These early mechanical manipulations revealed that velocity was independent of chromosome size, or load-independent, and led to influential models that invoked a "velocity-governor" regulating chromosome movement.…”
Section: Weak Machines and Entropic Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a spherical assembly with an averaged diameter of 7 lm (Keim et al, 2004b), traveling at 100 lm/s, the power consumed is *6.6 3 10 À16 J/s, which corresponds to *660 ATP molecules/s (Bray, 1992). This figure is relatively low if the typical cell metabolic rate, which is 10 7 ATP molecules/s (Nicklas, 1984), is considered. However, hydrodynamic interactions among the flagella may reduce the nominal efficiency to some extent.…”
Section: Discussionmentioning
confidence: 99%